The Effect of the Theo van Gogh Murder on House Prices in Amsterdam - Pieter A. Gautier; Arjen Siegmann; Aico van Vuuren (Tinbergen Institute, 2007)
This paper estimates the impact of the murder of film maker Theo vanGogh on November 2, 2004, on listed house prices in Amsterdam with aunique dataset. We use an hedonic-market approach to show that gen-eral attitudes towards Muslim minorities were negatively affected by themurder. Specifically, we test for an effect on listed house prices in neigh-borhoods where more than 25% of the people belong to an ethnic minor-ity from a Muslim country (type I). Relative to the other neighborhoods,house prices in type I neighborhoods decreased in 10 months by about av-erage 3%, with a widening gap over time. The results are robust to severaladjustments including changes in the control group. There is no signifi-cant difference in the time it takes for houses to be sold in type I versusother neighborhoods. Finally, people belonging to the Muslim minoritywere more likely to buy and less likely to sell a house in a type I neighbor-hood after the murder than before.
Keywords: C31; C41; R21; R23; R31; 330; Differences-in-differences; Terror; housing market; Öffentliche Sicherheit; Terrorismus; Islamisch; Immobilienpreis; Amsterdam